Contribution of information and communication technology (ICT) in country'S H-index - Farhadi, M.; Salehi, H.; Embi, M.A.; Fooladi, M.; Farhadi, H.; Aehaei Chadegani, A.; Ale Ebrahim, N. (2013)
The aim of this study is to examine the effect of Information and Communication Technology (ICT) development on country's scientific ranking as measured by H-index. Moreover, this study applies ICT development sub-indices including ICT Use, ICT Access and ICT skill to find the distinct effect of these sub-indices on country's H-index. To this purpose, required data for the panel of 14 Middle East countries over the period 1995 to 2009 is collected. Findings of the current study show that ICT development increases the H-index of the sample countries. The results also indicate that ICT Use and ICT Skill sub-indices positively contribute to higher H-index but the effect of ICT access on country's H-index is not clear.